ANALISIS PENGARUH SOCIAL MEDIA ADVERTISING, EWOM, DAN PEER GROUPS TERHADAP TRUST DAN PURCHASE INTENTION (Studi Kasus pada Konsumen Starbucks Pontianak) - B2041162024, YULITA SUHARSONO (Universitas Tanjungpura, 2019)
This research aims to examine and analyse the influences of social media advertising, eWOM, peer groups on trust and their impacts on purchase intention. This is an associative research to show the causative relation among variables. The hypotheses which were tested are the influences of social media advertising on trust, eWOM on trust, peer groups on trust, social media advertising on purchase intention, eWOM on purchase intention, peer groups on purchase intention, and trust on purchase intention. The survey was done towards 100 costumers of Starbucks Pontianak. This research was using purposive sampling technique. The respondents in this research must be 17 years old and above, be the followers of Starbucks accounts at LINE and Instagram, and had never tried the new products of Starbucks in this last 3 months. Data processing was done using WarpPLS 6.0. The data was then analysed by using structural equation model analysis. The results of this research showed that the influences of social media advertising and peer groups on trust are supported, but the influence of eWOM on trust is not supported. The influences of social media advertising and eWOM on purchase intention are supported, but the influence ofÂ peer groups on purchase intention is not supported. The influence ofÂ trust on purchase intention is supported. This research showed two different results from hypotheses test which do not support the previous researches.Keywords: sosmed advertising, eWOM, peer groups, trust